Organization of Work with Parents During the Formation of Local History Literacy of Children with Different Educational Needs in the Framework of Step by Step Technology - Nikitina, E. S.; Andreeva, N. V.; Shtern, O. V.; Gordeeva, E.V.; Kurovskiy, V. N. (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: The article analyzes the specifics of interaction between teachers and the parent community. The use of Step by Step technology and differentiated test control has been suggested as one of the ways to increase parents’ involvement in the educational process in the formation of local history literacy of children with different educational needs in primary school conditions. Materials and methods: the research was conducted on the basis of theoretical and empirical methods, the main of which was the analysis of interaction of participants of the educational process, and the research material was a variety of types of organization of interaction with parents. Findings: Interaction using Step by Step technology is seen as a key factor in organizing and optimizing the interaction of the educator with the parent community and students with different educational needs in primary school. Discussion and conclusions: the experience of theoretical and empirical research of the process of parental community involvement in the educational process of primary school using the Step by Step technology has been presented, the concepts of "poly subjective approach", "interaction" in the pedagogical context have been characterized.